2016
DOI: 10.1186/s12882-016-0339-y
|View full text |Cite
|
Sign up to set email alerts
|

Vegan-vegetarian low-protein supplemented diets in pregnant CKD patients: fifteen years of experience

Abstract: BackgroundPregnancy in women with advanced CKD becoming increasingly common. However, experience with low-protein diets in CKD patients in pregnancy is still limited.Aim of this study is to review the results obtained over the last 15 years with moderately restricted low-protein diets in pregnant CKD women (combining: CKD stages 3-5, proteinuria: nephrotic at any time, or > =1 g/24 at start or referral; nephrotic in previous pregnancy). CKD patients on unrestricted diets were employed for comparison.MethodsStu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 68 publications
7
50
0
Order By: Relevance
“…Even in this case, the experimental dietary regimen was tolerated and more interestingly the incidence of SGA babies was significantly lower in the diet group, while during the long-term follow-up, the children did not present health or socialization problems [33]. A subsequent analysis that compared 36 on diet CKD pregnancies vs. 47 CKD control cases on unrestricted diet in a follow-up of 15 years, confirmed that the incidence of SGA and/or extremely preterm babies (<28th week) was significantly lower in on-diet mothers than in the controls, suggesting again a possible positive effect of a plant-diet in CKD subjects [34]. The same group has more recently published a report focused on the same plant-based diet in three pregnant patients with focal segmental glomerulosclerosis.…”
Section: Clinical Experiencesmentioning
confidence: 84%
“…Even in this case, the experimental dietary regimen was tolerated and more interestingly the incidence of SGA babies was significantly lower in the diet group, while during the long-term follow-up, the children did not present health or socialization problems [33]. A subsequent analysis that compared 36 on diet CKD pregnancies vs. 47 CKD control cases on unrestricted diet in a follow-up of 15 years, confirmed that the incidence of SGA and/or extremely preterm babies (<28th week) was significantly lower in on-diet mothers than in the controls, suggesting again a possible positive effect of a plant-diet in CKD subjects [34]. The same group has more recently published a report focused on the same plant-based diet in three pregnant patients with focal segmental glomerulosclerosis.…”
Section: Clinical Experiencesmentioning
confidence: 84%
“…Moreover, most of the children of the vegetarian women had normal intrauterine growth and developed normally between 1 month and 7.5 years from delivery [77]. The review of the results obtained during 15 years of treatment of pregnant CKD women on moderately restricted low-protein diets confirms that such a diet is a safe option in the management of pregnant CKD patients [78]. A trend towards better preserved fetal growth was observed.…”
Section: The Safety Of Vegetarian Dietmentioning
confidence: 99%
“…In advanced CKD stages and under dialysis, protein recommendations for adults with CKD may be used, while adding the extra needs of pregnancy. In stages 3-5, a moderate-protein-restricted plant-based diet (0.6-0.8 g/kg/ day of protein) plus keto-analogs (1 tablet/8-10 kg) showed a lower frequency of early preterm delivery, very low birth weight (LBW) (<1500 g) and SGA infants [20][21][22][23]. In different reported case series of pregnant women under HD, a protein intake of 1.2-1.5 g/kg of ideal body weight/day plus 6-10 g/day was related with optimal plasmatic nitrogen compounds levels, controlled blood pressure, reduced proteinuria, and improved plasmatic albumin and phosphorus [14,15,18].…”
Section: Protein Recommendationsmentioning
confidence: 99%